Opsang til det hele – Om sang og politik hos Mladen Dolar og Slavoj Žižek - Hansen, Brian Benjamin (Slagmark - Tidsskrift for idéhistorie, 2018)
The article presents and is an introduction to a theory of the voice, as it is put forth by Slavoj Žižek and Mladen Dolar, and in the discourse of psychoanalysis. It is developed as a reading of the ‘incident in London’, where Žižek wanted to engage the audience of an academic conference in a performance of The Internationale. The article is thus also about a possible connection of singing and politics.